2014
DOI: 10.4236/jeas.2014.43009
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Contamination in Greenhouse Soils and Vegetables in Guanzhong, China

Abstract: This study used a flame atomic absorption spectrometer (FAAS) and atomic fluorescence spectrophotometer (AFS) to detect the concentrations of chromium (Cr), cadmium (Cd), lead (Pb), hydrargyrum (Hg) and arsenic (As) in soils and three genotypes of vegetables in greenhouse, as well as analyzed the physical and chemical properties of soils, including soil pH, soil organic matter (OM), basic nutrients, electrical conductivity (EC) and cation exchange capacity (CEC) in Guanzhong areas, Shaanxi province, China. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
3
3
0
Order By: Relevance
“…The mean comparison between the two depths indicated that the soil pH at 1–10 cm (5.87) is higher than the soil depth of 10–20 cm (5.55) (Figure 2). The result is in line with the findings of [46,47], whereas the result is different from the findings of [48]. According to the classification of soil pH grade, the pH value of (<5) indicated slightly acidic, (5–6.5) mildly acidic, (6.5–7.5) neutral, (7.5–8.5) mildly alkaline and (>8.5) indicated strongly alkaline [49].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The mean comparison between the two depths indicated that the soil pH at 1–10 cm (5.87) is higher than the soil depth of 10–20 cm (5.55) (Figure 2). The result is in line with the findings of [46,47], whereas the result is different from the findings of [48]. According to the classification of soil pH grade, the pH value of (<5) indicated slightly acidic, (5–6.5) mildly acidic, (6.5–7.5) neutral, (7.5–8.5) mildly alkaline and (>8.5) indicated strongly alkaline [49].…”
Section: Resultssupporting
confidence: 92%
“…The relationships between trace elements and soil properties indicated that soil pH has a weak positive correlation with Fe, Ni, Cu, As, Sb, Cd and Pb, whereas a negative correlation with Cr, Co, Zn and Hg. The same finding was reported by [47], for Cr, As, Hg and Pb from Guangzhou (China). TOC had a negative correlation with Co, As, Sb, Cd and Hg, and a weak correlation with Cr, Fe, Ni, Cu, Zn and Hg.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Contamination of greenhouse soils by heavy metals as a result of long-term use of fertilizers and pesticides in food crops production becomes more and more intense, resulting in harmful effects on human health through consumption of food crops grown on these soils (Liu et al, 2014). Thus, it is imperative to reduce heavy metal contamination in greenhouse soils, and in order to achieve this goal, legislation of some developed countries has set tolerance limits on heavy-metal additions (fertilizers and biosolids) to soils.…”
Section: Discussionmentioning
confidence: 99%
“…The content of soil soluble salt in greenhouse vegetable land in Shanghai reached nearly four times the values in open fields (Li et al, 2011) while the contents of available nitrogen (N) and Olsen-P in Shanxi exceeded 1000 mg/kg and 130 mg/kg, respectively. The ratios of N, P, and K have also become seriously imbalanced in some greenhouse soils in Shanxi (Liu et al, 2014), Beijing (Chen et al, 2004), Liaoning (Meng et al, 2000), and Gansu (Kong et al, 2014;Bai et al, 2015). The large volumes of agrochemicals used in greenhouses have led to soil quality deterioration (Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%